1 cm2 Organic Photovoltaic Cells for Indoor Application with over 20% Efficiency. Issue 42 (6th September 2019) - Cui, Yong; Yao, Huifeng; Zhang, Tao; Hong, Ling; Gao, Bowei; Xian, Kaihu; Qin, Jinzhao; Hou, Jianhui
Abstract: Organic photovoltaic (OPV) technologies have the advantages of fabricating larger‐area and light‐weight solar panels on flexible substrates by low‐cost roll‐to‐toll production. Recently, OPV cells have achieved many significant advances with power conversion efficiency (PCE) increasing rapidly. However, large‐scale solar farms using OPV modules still face great challenges, such as device stability. Herein, the applications of OPV cells in indoor light environments are studied. Via optimizing the active layers to have a good match with the indoor light source, 1 cm 2 OPV cells are fabricated and a top PCE of 22% under 1000 lux light‐emitting diode (2700 K) illumination is demonstrated. In this work, the light intensities are measured carefully. Incorporated with the external quantum efficiency and photon flux spectrum, the integral current densities of the cells are calculated to confirm the reliability of the photovoltaic measurement. In addition, the devices show much better stability under continuous indoor light illumination. The results suggest that designing wide‐bandgap active materials to meet the requirements for the indoor OPV cells has a great potential in achieving higher photovoltaic performance. Abstract : Organic photovoltaic (OPV) cells promise to have a good photovoltaic performance under the indoor light environment. Via optimizing the active layers, 1 cm 2 OPV cells are fabricated and a top power conversion efficiency of 22% under 1000 lux illumination is demonstrated.